Comparison Of Dragon Fruit And Guava Juice With Iron Tablets In Increasing Hemoglobin Levels In Anemic Adolescent Girls - Laila, Ani; Permatasari, Septi Indah; Rahmalia, Meizy; Susanti, Ari (Poltekkes Kemenkes Riau, 2023)
Anemia is a health problem among teenagers, especially young women in Indonesia. As many as 27.2% of adolescent girls experience anemia. Efforts to overcome anemia in adolescents are carried out by meeting the iron requirements needed. This study aims to determine the comparison of dragon juice and guava juice with iron tablets in increasing hemoglobin levels in adolescent girls. This research is a quasi-experimental study with a two group post test design. Samples were taken purposively, with a total of 20 young women. Based on the results of the Independent T-test, there was a comparison of dragon fruit juice and guava juice with iron tablets (p=0.013). It is hoped that young women regularly consume nutrition containing iron and Vitamin C as needed to prevent anemia in young women.